Stronger than you know [large type] - Foster, Lori, 1958- (Foster, Lori, 1958- McKenzies of Ridge Trail, 2022)
"Kennedy Brooks has spent years learning how to protect herself, and empowering other women to do the same. Still, there are some hazards that can't be predicted. That includes Reyes McKenzie, who owns her local gym. Strong, capable, and watchful, he seems like the one man who might understand her past. For once, Kennedy is tempted to let her guard down - something she's vowed never to do. The moment petite, fiercely determined Kennedy walked into his gym, Reyes knew that she carried secrets. What he didn't expect was that she could tell the same about him. When trouble tracks her down, she turns to Reyes, unleashing a maelstrom of protective instinct and mutual desire. But will her need for him end when the danger does, or will they take the ultimate risk - on each other?"--